2021
DOI: 10.3390/ijms22031125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maturation and Vitrification Time of Human GV Oocytes on the Metaphase Plate Configuration

Abstract: The combination of in vitro maturation (IVM) techniques and oocyte vitrification (OV) could increase the number of useful oocytes in different types of patients. IVM and subsequent OV is the most widely used clinical strategy. Would the results improve if we reverse the order of the techniques? Here, we evaluated survival, in vitro maturation, time to extrude the first polar body (PB), and the metaphase plate configuration of human prophase I (GV) oocytes before or after their vitrification. Specific, 195 GV o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…The slightly better outcomes observed in vitrified MII oocytes could indicate that vitrification is more deleterious in earlier immature states. Two previous works using GVs that were vitrified before and after IVM did not show an evident impact in the meiotic spindle constitution [ 20 , 21 ]. In particular, one of these works also reported a slightly detrimental effect on the ultrastructural organization of cytoplasmic components of mature oocytes generated from vitrified and warmed GVs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The slightly better outcomes observed in vitrified MII oocytes could indicate that vitrification is more deleterious in earlier immature states. Two previous works using GVs that were vitrified before and after IVM did not show an evident impact in the meiotic spindle constitution [ 20 , 21 ]. In particular, one of these works also reported a slightly detrimental effect on the ultrastructural organization of cytoplasmic components of mature oocytes generated from vitrified and warmed GVs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…GV [ 52 ] or MII oocytes have fewer CPAs and water permeability than zygotes and later-stage embryos [ 53 ]. The vitrification of denuded MII oocytes could generate alterations in the plasma membrane, mitochondrial distribution, meiotic spindle, and chromosomes [ 54 ]. Rojas et al [ 28 ] reported that vitrified MII oocytes show spindle abnormalities because chromosomes are exposed directly to CPAs.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that alterations to mitochondria redistribution, CG migration, global DNA methylation expression and, especially, spindle and chromosome organization were reported [18]. By contrast, a recent study of the metaphase plate by confocal microscopy revealed that immature human oocytes subjected first to vitrification and then to in vitro maturation up to the MII-stage showed a higher percentage of normal metaphase spindle configuration if compared to those matured in vitro first and then vitrified [19]. These discrepancies may be solved with the aid of electron microscopy (EM), the gold standard in revealing the ultrastructural characteristics of immature oocytes.…”
Section: Gv-stage Oocytes As a Potential Resource In Artsmentioning
confidence: 96%
“…The IVM of these "leftover" immature (GV-stage) oocytes with developmental competence represents a potential tool for ART patients, in particular for poor responders, PCOS women, and for avoiding the side effects of OHSS [29,63,64]. While discarded in the past, today GV oocytes can be cryopreserved before or after IVM, thus increasing the opportunity for achieving a pregnancy [19,29]. However, the successful application of IVM on leftover oocytes is still facing issues, mainly due to defects in the cytoplasmic maturation or asynchronous cytoplasmic and nuclear maturation [30,46,65].…”
Section: In Vitro Maturation (Ivm)mentioning
confidence: 99%